2013
DOI: 10.1103/physrevd.87.084058
|View full text |Cite|
|
Sign up to set email alerts
|

Isolated and binary neutron stars in dynamical Chern-Simons gravity

Abstract: In Ref.[1], the Chern-Simons correction to the osculating orbital elements due to the dipole-dipole interaction for the scalar field was derived in Eq. (130) by integrating out the interaction Lagrangian, which was taken to be the kinetic term for the scalar field [Eq. (122) in [1]], using the scalar field solution. However, such kinetic term only leads to the left-hand side of the evolution equation for the scalar field, i.e.where J is the effective source term of the scalar field equation [2]. In order to o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 148 publications
(308 reference statements)
16
108
0
Order By: Relevance
“…Just as in the case of EdGB gravity, the calculation of (monopole) scalar charges (or sensitivities) is also crucial here to understand the emission of scalar radiation. The asymptotic behavior of the scalar field at spatial infinity has revealed that black holes have a rather large scalar charge [19,100], while the scalar charge of neutron stars is greatly suppressed [23,107]; the derivation of the latter result follows closely the explanation in EdGB gravity presented in the previous section. As in the EdGB case, this means that stars have a tiny scalar field, but this grows upon gravitational collapse, until the charge asymptotes that of isolated black holes.…”
Section: Dynamical Chern-simons Gravitysupporting
confidence: 68%
“…Just as in the case of EdGB gravity, the calculation of (monopole) scalar charges (or sensitivities) is also crucial here to understand the emission of scalar radiation. The asymptotic behavior of the scalar field at spatial infinity has revealed that black holes have a rather large scalar charge [19,100], while the scalar charge of neutron stars is greatly suppressed [23,107]; the derivation of the latter result follows closely the explanation in EdGB gravity presented in the previous section. As in the EdGB case, this means that stars have a tiny scalar field, but this grows upon gravitational collapse, until the charge asymptotes that of isolated black holes.…”
Section: Dynamical Chern-simons Gravitysupporting
confidence: 68%
“…All of the results that we present will be given in terms of powers of the dimensionless coupling ( /GM ). We will also compare to known post-Newtonian results [24], that were presented in terms of α YSYT…”
Section: Summary and Scalingmentioning
confidence: 95%
“…The PPN parameters for a non-dynamical version of the theory with α = κ and β = 0 are identical to those of GR; however, there is an additional, parity-even potential in the g 0 i component of the metric that does not appear in the standard PPN framework, given by Unfortunately, the non-dynamical version has been shown to be unstable [137], while the dynamical version is sufficiently complex that its observable consequences have been analyzed for only special situations [6, 444]. Alexander and Yunes [5] give a thorough review of Chern-Simons gravity.…”
Section: Metric Theories Of Gravity and The Ppn Formalismmentioning
confidence: 99%